2008
DOI: 10.1159/000140611
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cognitive Outcome of Delirium in Elderly Hip Surgery Patients

Abstract: Objective: To study the outcome of delirium in elderly hip surgery patients. Design: Prospective matched controlled cohort study. Hip surgery patients (n = 112) aged 70 years and older, who participated in a controlled clinical trial of haloperidol prophylaxis for delirium, were followed for an average of 30 months after discharge. Patients with a diagnosis of dementia or mild cognitive impairment (MCI) were identified using psychiatric interviews. Proportions of patients with dementia/MCI were compared across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(30 citation statements)
references
References 64 publications
1
28
0
1
Order By: Relevance
“…The strengths of the study are that the patients were all acutely admitted, while other studies included patients undergoing elective hip arthroplasty [12,15]. We used validated and robust methods of assessing delirium, ADL dependency and previous cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strengths of the study are that the patients were all acutely admitted, while other studies included patients undergoing elective hip arthroplasty [12,15]. We used validated and robust methods of assessing delirium, ADL dependency and previous cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Poor cognition is an important risk factor for delirium [4,10], but the impact of an episode of delirium upon the subsequent development of dementia is less well understood [11]. Several studies have suggested that delirium associated with hip fracture may predict dementia [12,13,14,15,16], but no studies have satisfactorily assessed the patients’ prefracture cognitive status. Though only patients free from a diagnosis of dementia have been included in previous studies, no study has performed a formal evaluation of the patients’ cognitive status prior to the fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, severe neuropsychological symptoms triggered by peripheral infection can develop without direct bacterial invasion into the brain spreading from peripheral organs (van Gool et al, 2010) and without signs of sepsis (Ebersoldt et al, 2007). A prospective matched control study has shown a strong association between dementia and postoperative delirium in elderly people who underwent hip surgery, suggesting a link between systemic inflammation induced by peripheral intervention and dementia-associated psychiatric symptoms (Kat et al, 2008). However, at present, specific mechanisms for the susceptibility of demented patients to infection-triggered neuropsychological symptoms have not been proposed.…”
Section: Inflammation and Dementia-associated Behavioral Disturbancementioning
confidence: 99%
“…Its course is typically acute and fluctuating, and its etiology multifactorial, triggered by underlying medical conditions or drugs [2]. It is associated with negative outcomes, such as decline in cognitive and functional status [3][4][5], prolonged hospitalization, increased morbidity and mortality, and finally higher health care costs [2,6,7]. It is also a major source of distress for patients, caregivers, and health care providers [8,9].…”
Section: Introductionmentioning
confidence: 99%